2008
DOI: 10.1136/jnnp.2008.149708
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death and clinical grading criteria in a cohort of amyotrophic lateral sclerosis cases undergoing autopsy from the Scottish Motor Neurone Disease Register

Abstract: Within our cohort, MND contributes to death in the majority of cases and there is excellent clinicopathological correlation, irrespective of the clinical grading criteria used. However, the autopsy rate is low (4%) and further larger studies are required to identify heterogeneity within the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 20 publications
(16 reference statements)
2
47
1
2
Order By: Relevance
“…8 In a cohort of 40 consecutive patients with ALS, Sorenson et al 18 observed the occurrence of aspiration pneumonia in 5 cases (13%). In an autopsy cohort of patients with ALS, Kurian et al 22 found a similar number of occurrences, with aspiration pneumonia being listed as the cause of death in 11% of cases, bronchopneumonia in 41%, and respiratory failure in 9%. Death was directly attributable to motor neuron disease in 11% of cases, cardiac causes in 14%, malignancies in 5%, and other causes in the remaining 9% of patients.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…8 In a cohort of 40 consecutive patients with ALS, Sorenson et al 18 observed the occurrence of aspiration pneumonia in 5 cases (13%). In an autopsy cohort of patients with ALS, Kurian et al 22 found a similar number of occurrences, with aspiration pneumonia being listed as the cause of death in 11% of cases, bronchopneumonia in 41%, and respiratory failure in 9%. Death was directly attributable to motor neuron disease in 11% of cases, cardiac causes in 14%, malignancies in 5%, and other causes in the remaining 9% of patients.…”
Section: Introductionmentioning
confidence: 75%
“…Death was directly attributable to motor neuron disease in 11% of cases, cardiac causes in 14%, malignancies in 5%, and other causes in the remaining 9% of patients. 22 Excessive drooling also limits tolerance of NIV, which has been consistently shown to increase the life expectancy and quality of life of patients with ALS. [23][24][25][26][27][28][29][30][31][32][33] Thus, a successful management of sialorrhea may prolong NIV tolerance in ALS, 34 resulting in enhanced survival.…”
Section: Introductionmentioning
confidence: 99%
“…Most resources available on amyotrophic lateral sclerosis identify the leading cause of clinical death as respiratory failure [1], [9]- [11]. The pathological cause of death is diagnosed through laboratory analysis of bodily fluids and/or tissues.…”
Section: Primary Cause Of Deathmentioning
confidence: 99%
“…To date, very little literature exists identifying the cause of death in ALS patients through post mortem pathological analysis. It is estimated the autopsy rate among ALS patients is approximately four percent [9]. Within the body of research that does exist, the primary cause of death in more than 70 percent of the cases is either broncho-pneumonia or aspiration pneumonia [1], [9]- [11].…”
Section: Primary Cause Of Deathmentioning
confidence: 99%
“…Others variables beyond number of hours/day, namely the ventilation settings of NIV equipment, need be evaluated about their potential role on functional and survival outcomes, and it has never been published. In addition, recent studies have suggested other causes of death in ALS [6][7][8][9][10][11], which reinforces the need to clarify whether respiratory disturbances and discomfort with NIV are present near the time of death, and whether they could possibly be amenable to corrections. We aimed to investigate the prognostic factors for functional decline among ALS patients under NIV, considering all variables recorded by the equipment software [12] from initial adaptation until to death or end of study.…”
Section: Introductionmentioning
confidence: 99%